Răspuns :
1) a+b+c= 3932
b= a-1330
c = a- 1740
a + a-1330+ a -1740 = 3932
3a-3070=3930
3a= 7002
a = 2334
b= 1004
c= 594
2) a+b+c= 163
(a+b)-c= 67 => a+b = 67 +c
(b+c) - a=37 => b+c = 37+a
2a + 37 = 163
2a = 126
a= 63
2c + 67 = 126
2c= 96
c= 48
48+63+b= 163
b= 163 - 111
b = 52
b= a-1330
c = a- 1740
a + a-1330+ a -1740 = 3932
3a-3070=3930
3a= 7002
a = 2334
b= 1004
c= 594
2) a+b+c= 163
(a+b)-c= 67 => a+b = 67 +c
(b+c) - a=37 => b+c = 37+a
2a + 37 = 163
2a = 126
a= 63
2c + 67 = 126
2c= 96
c= 48
48+63+b= 163
b= 163 - 111
b = 52